[18F] FBB cortical uptake is not related to the age of onset of Alzheimer's disease. Issue 2 (February 2020) - Chiaravalloti, Agostino; Barbagallo, Gaetano; Castellano, Anna Elisa; Ricci, Maria; Ciccariello, Gabriele; Ursini, Francesco; D'Ascenzo, Nicola; Xie, Quingguo; Schillaci, Orazio
Abstract : Aim: To investigate the relationships between amyloid burden in brain and the age of onset of Alzheimer's disease. Materials and methods: We examined 60 patients with clinical diagnosis of Alzheimer's disease. Of them, 22 were early-onset of Alzheimer's disease and 38 were late-onset of Alzheimer's disease. All of them underwent a brain PET scan 90 minutes after the injection of 4-[(E)-2-[4-[2-[2-(2-fluoranylethoxy)ethoxy]ethoxy]phenyl]ethenyl]-N-methylaniline ([ 18 F] FBB); 300 ± 10 MBq). Relationships between amyloid burden in brain and age of onset of Alzheimer's disease were assessed by means of statistical parametric mapping version 12. Results: There were no significant differences [ 18 F] FBB uptake between early-onset of Alzheimer's disease and late-onset of Alzheimer's disease patients. Conclusion: In our study group, the age of onset is not related to brain amyloid burden in Alzheimer's disease patients.